2009
DOI: 10.1590/s0103-50532009000500014
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon oxidation catalyzed by iron and manganese porphyrins anchored on aminofunctionalized supports

Abstract: As metaloporfirinas de segunda geração (MePs), cloreto de [5,10,15,20-tetraquis(pentafluorofenil)porfirinaferro(III)], FeP, e cloreto de [5,10,15,20-tetraquis(pentafluorofenil)porfirinamanganês(III)], MnP, foram covalentemente ancoradas em suportes aminofuncionalizados, com o objetivo de preparar catalisadores sólidos seletivos para a oxidação de compostos orgânicos. Montmorillonita K10 funcionalizada com 3-aminopropiltrietoxissilano (Mont1) ou com 3-cloropropiltrietoxissilano seguida por reação com 1,6-diamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Substitution of the p-fluorine atoms with a bulkier group may account for this result.As reported by Cook[89] in the case of heptane oxidation catalyzed by (5, 10, TTPPP)]OAc, in homogeneous medium, the introduction of bulky substituents can promote oxidation at the terminal positions. Nappa et al[78] observed this sameThe introduction of bulky groups favors the approach of terminal carbons to the active catalytic center. However, the carbons at position 2 of hexane are more exposed, which explains the larger oxidation at this position.…”
mentioning
confidence: 77%
See 3 more Smart Citations
“…Substitution of the p-fluorine atoms with a bulkier group may account for this result.As reported by Cook[89] in the case of heptane oxidation catalyzed by (5, 10, TTPPP)]OAc, in homogeneous medium, the introduction of bulky substituents can promote oxidation at the terminal positions. Nappa et al[78] observed this sameThe introduction of bulky groups favors the approach of terminal carbons to the active catalytic center. However, the carbons at position 2 of hexane are more exposed, which explains the larger oxidation at this position.…”
mentioning
confidence: 77%
“…However, Assis et al [78] observed that FeP1 was more efficient than the corresponding MnP and attributed this fact to the presence of Mn(II) in the catalyst. with the tetra-substituted series ( Table 2, runs 6-10 for FeP6, 14-17 for MnP6, and 19-23 for CuP6).…”
Section: (Z)-cyclooctenementioning
confidence: 99%
See 2 more Smart Citations
“…More recently, porous metalloporphyrin networks have proven to be potentially applicable as efficient heterogeneous catalysts 5 after immobilization in organic amorphous polymers, amorphous inorganic matrices, or crystalline inorganic materials such as silica, 6,7 zeolites, 8,9 clay from the smectite group (montmorillonite), [10][11][12] layered double hydroxides, 13,14 tubular and fibrous matrices, 15 silica matrix obtained by the sol-gel process, among others. [16][17][18][19][20][21][22][23] This versatile class of molecules is efficient and selective for the heterogeneous catalytic hydroxylation and epoxidation of a wide variety of organic substrates.…”
Section: Introductionmentioning
confidence: 99%